The Influence of Managerial Skill and Creativity on Decision Making in Public Junior High Schools of Tangerang City And Regency - Syafa'at Ariful Huda (Research in Social Sciences and Technology- OpenED Network, 2018)
The objectiveof this research is to study the effect of managerial skilland creativity onprincipals’sdecision making in Public Junior High Schoolof Tangerang Cityand Regency. Thisresearch used survey method. The samples of this research were 60 persons selected randomly.Technique of data collection tools is using instrument in the questionnaire.The data were analyzed by using descriptive statistics and path analysis in inferential statistics. The result of the research conclucedthat: managerial skill and creativity had direct effect on principal decision making of Public Junior High School. Therefore to improve principal decision making,managerial skill and creativity should be improved.